Dysphoric milk ejection reflex among Japanese mothers: a self-administered survey - Yukako Moriyama; Yuko Nakao; Naoko Yamamoto; Toshimichi Oki (BMC, 2024)
Abstract Background The dysphoric milk ejection reflex (D-MER) is a reflex that causes temporary discomfort during milk ejection. D-MER develops due to the effects of hormones involved in lactation, and it has been reported that it is a physiological symptom different from postpartum depression, but the actual situation is unknown in Japan. Methods This study was conducted using a self-administered, anonymous survey of mothers of children who had undergone health checkups at three years of age at five health centers in Kagoshima city and aimed to clarify the reality and perceptions of mothers regarding D-MER. The survey period was from May to September, 2022. The questionnaires were distributed to 389 mothers, and 216 (55.5% recovery rate) responses were received, of which 202 (valid response rate 93.5%) were included in the analysis. Results Regarding the experience of D-MER, 202 mothers in the study population had given birth to a total of 403 children and experienced D-MER when breastfeeding 62 children (15.4%). Of the 202 mothers included in the analysis, 47 (23.3%) answered that they had experienced D-MER with at least one child while breastfeeding. Sixty-six mothers (32.7%) knew about D-MER. Compared to those who had not experienced D-MER, those who had experienced D-MER had significantly higher scores on the items related to having had trouble breastfeeding (odds ratio (OR]: 3.78; 95% confidence interval (CI]: 1.57, 9.09) and knowing about D-MER (OR 2.41; 95% CI 1.20, 4.84). Regarding symptoms, irritability (n = 24, 51.1%), anxiety (n = 22, 46.8%), and sadness (n = 18, 38.3%) ranked high. Coping strategies included distraction, focusing on the child, and, in some cases, cessation of breastfeeding. Thirty mothers (63.8%) answered that they did not consult anyone, citing reasons such as a belief that no one would be likely to understand their symptoms, and that they could not sufficiently explain their symptoms. Conclusion The low level of awareness of D-MER suggests that it is necessary to inform and educate mothers and the public about the physiological symptoms of D-MER. Moreover, it is necessary to listen to the feelings of mothers with D-MER and support them in coping with their symptoms.